Numerasi Siswa SMA dalam Menyelesaikan Soal AKM Konten Data dan Ketidakpastian Ditinjau dari Gaya Kognitif Reflektif Impulsif - Putri, Anggi Adelia; Kurniasari, Ika (Universitas Negeri Surabaya, 2025)
Numeracy is the ability to access, use, and interpret mathematical concepts, procedures, facts, and tools to solve problems in everyday life contexts. The indicators in this study refer to the numeracy process, which includes identifying, finding, or accessing, acting/using, interpreting, evaluating/analyzing, and communicating. This study aims to describe the numeracy of senior high school students in solving AKM problems in the context of data and uncertainty in term of reflective and impulsive cognitive styles. This research uses a qualitative descriptive method. The subjects of this study are eleventh-grade senior high school students consisting of one reflective and one impulsive student. The instruments of this research are Matching Familiar Figures Test (MFFT), a mathematics ability test, a numeracy test, and interviews. Results of the MFFT and mathematics ability test were used to determine the subjects. The numeracy test results were analyzed based on numeracy indicators. Based on the analysis, this study found that reflective students carried out all numeracy processes, including identifying, locating or accessing information, using appropriate procedures, interpreting results, evaluating or analyzing, and communicating on knowing, applying, and reasoning questions. However, they still have difficulty in communicating information verbally, especially in conveying the reasons for choosing the way to solve the problem. Impulsive students also performed all numeracy processes on the same types of questions but still have difficulty in communicating orally and in writing. Moreover, in reasoning questions, impulsive students applied inappropriate strategies during the using process, leading to incorrect answers.